Atmospheric Icing of Power Networks - Farzaneh, Masoud; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
Atmospheric ice takes a wide range of fascinating forms, all beautiful in their own ways but many posing severe risk to the security of overhead networks for electric power, communications and other systems. This comprehensive book documents the fundamentals of atmospheric icing and surveys the state of the art in eight chapters, each written by a team of experienced and internationally renowned experts. The treatment is detailed and richly illustrated. The presentation follows a logical sequence, starting with the icing climate and meteorological conditions, proceeding through development of observations and models of accretion and release of ice and heavy snow, then considering static and dynamic mechanical loads, the effects of ice and snow on electrical insulation, de-icing, ice prevention and mitigation methods. The statistical analysis of icing data and the mathematical and numerical modelling support appropriate mechanical and electrical design processes for icing conditions on overhead lines. Technical specialists, researchers and students in engineering and environmental science will all find value throughout the text.
Modern Meteorology and Atmospheric Icing -- Statistical Analysis of Icing Event Data for Transmission Line Design Purposes -- Numerical Modelling of Icing on Power Network Equipment -- Wet Snow Accretion on Overhead Lines -- Effect of Ice and Snow on the Dynamics of~Transmission Line Conductors -- Anti-icing and De-icing Techniques for Overhead Lines -- Effects of Ice and Snow on the Electrical Performance of Power Network Insulators -- Design of Transmission Lines for Atmospheric Icing.
Keywords: Energy systems; Civil engineering; Atmospheric sciences; Environmental sciences; Computer simulation; Energy; Energy Systems; Civil Engineering; Atmospheric Sciences; Math. Appl. in Environmental Science; Simulation and Modeling; Energy, general